Dictionary of word and phrase origins - Rees, Nigel (Cassell, 1994)
Why do we say a person is the "spitting image" of someone else, or "take a rain check"? These questions are rarely answered by conventional dictionaries, but this book takes a wide-ranging approach to problems of etymology, challenging a few long-held theories on the way.